2020
DOI: 10.1126/science.aba2412
|View full text |Cite
|
Sign up to set email alerts
|

Gas chromatography–mass spectrometry analyses of encapsulated stable perovskite solar cells

Abstract: Although perovskite solar cells have produced remarkable energy conversion efficiencies, they cannot become commercially viable without improvements in durability. We used gas chromatography–mass spectrometry (GC-MS) to reveal signature volatile products of the decomposition of organic hybrid perovskites under thermal stress. In addition, we were able to use GC-MS to confirm that a low-cost polymer/glass stack encapsulation is effective in suppressing such outgassing. Using such an encapsulation scheme, we pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
332
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 360 publications
(354 citation statements)
references
References 73 publications
4
332
0
Order By: Relevance
“…Glass-glass encapsulation as well as the use of edge-seal technology have been proposed, although low perovskite decomposition temperature presents a challenge for selecting a benign sealant. The authors demonstrated how such encapsulation provides a 104 Although, undoubtedly, encapsulation helps to reduce the moisture ingress into the photovoltaic device, the stability of the photoabsorber, selective layers and cathode materials still needs to be considered and effective strategies to passivate perovskite and mitigate decomposition reactions need to be developed besides encapsulation. For example, Liu et al have demonstrated implementation of interfacial engineering in perovskite solar modules, which provided a moderate operational stability.…”
Section: View Article Onlinementioning
confidence: 99%
“…Glass-glass encapsulation as well as the use of edge-seal technology have been proposed, although low perovskite decomposition temperature presents a challenge for selecting a benign sealant. The authors demonstrated how such encapsulation provides a 104 Although, undoubtedly, encapsulation helps to reduce the moisture ingress into the photovoltaic device, the stability of the photoabsorber, selective layers and cathode materials still needs to be considered and effective strategies to passivate perovskite and mitigate decomposition reactions need to be developed besides encapsulation. For example, Liu et al have demonstrated implementation of interfacial engineering in perovskite solar modules, which provided a moderate operational stability.…”
Section: View Article Onlinementioning
confidence: 99%
“…[317] In addition, PSCs should be subject to strict testing standards such as those in accordance with the IEC 61215:2016 standards, which will further strengthen the viability of commercial PSCs. During the preparation of this review, Shi et al [318] used an encapsulation scheme using a mixed-cation mixed-halide perovskite absorber layer which survived more than 1800 h of damp heat test and 75 cycles of humidity freeze test, exceeding the requirement of IEC61215:2016. This exceptional achievement of stability and durability further demonstrates the exciting future of perovskite research.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…[70,71] Packaging/ encapsulation wrapped around the whole device can efficiently improve the device resistance against the attack of H 2 O/O 2 and prevent the escape of component from the perovskite layer. [72,73] Recently, Shi et al demonstrated a MA-containing PSC surviving after over 1800 h of damp heat test and 75 cycles of humidity freeze test by using a polymer/glass stack pressuretight encapsulation to effectively suppress the outgassing, [74] which clearly revealed the importance of preventing component escape for the device stability. One can find the related works in the recent reviews on PSC encapsulation.…”
Section: Imentioning
confidence: 99%
“…This may be an effective way to protect perovskites against the attack of H 2 O/O 2 and prevent ion/molecular escaping from the perovskite layer simultaneously, leading to robust absorber layer and long-term stable PSCs. [70][71][72][73][74] Thus, here, we also describe the progress on the barriers inserted between perovskite layer and the top electrode layer in this review. In this section, the barriers are discussed according to the classification of barrier materials including organic barriers and inorganic barriers.…”
Section: Barriers Design At Interface Atop Perovskite Layer Against Hmentioning
confidence: 99%